Blue Nile flow, sediment and impact of watershed interventions: case of Gumera Watershed - Awulachew, Seleshi Bekele; Tenaw, M.; Steenhuis, Tammo S.; Easton, Z.M.; Ahmed, A.; Bashar, K.E. (2008)
High population pressure, inappropriate agricultural policies, improper land-use planning, over-dependency on agriculture as source of livelihood and extreme dependence on natural resources are inducing deforestation, overgrazing, expansion of agriculture to marginal lands and steep slopes, declining agricultural productivity and resource-use conflicts in many parts of Blue Nile. Increased land degradation from poor agricultural practices and erosion results in increased siltation and the reduced water quality in the river basin. The rainfall, runoff and sediment are highly variable both in time and space. Poor water and land management upstream severely affect runoff characteristics and the quality of water reaching downstream. The result is a downward spiral of poverty and food insecurity for millions of people both within the upper catchment and downstream across international borders. Quantification of the erosion, sedimentation processes and evaluation of impacts of interventions are difficult tasks. This paper schematizes the Blue Nile Basin (BNB) at various spatial levels as micro watershed, watershed, sub-basin to basin. It considers a particular watershed to model runoff, sediment and impact of watershed intervention. The result shows that runoff can be reasonably simulated with calibration of R2=0.87 and validation of result of 0.82, and comparable sediment modelling results. The study also demonstrates, by undertaking spatial analysis using topographic, soil and land use parameters it is possible to identify the high sediment risk sub-watersheds. Impact of typical watershed intervention using various widths of vegetative filter and application on high erosion risk watersheds show reduction of sediment yield from 52% to 74%